UJI EFEK ANTIHIPERGLIKEMIK EKSTRAK ETANOL DAUN KACAPIRING (Gardenia augusta, Merr) PADA TIKUS PUTIH JANTAN GALUR WISTAR - Farida Baroroh; Nurfina Aznam; Hari Susanti (Pharmaciana, 2011)
Kaca piring leaf (Gardenia augusta Merr.) was often used in traditional drugs fortreatment diabetes mellitus. This research aim to know the antihiperglycemic effectethanolic extract of kacapiring leaf on white rats male strain of Wistar and how muchantihiperglycemic effect compared with glibenklamid. This study used oral glucosetolerance test method with loading glucose 4,5 g/kgW. Tested animal where 24 whitemale rats strain of Wistar age 2-3 months with weight 180-250 gram, devided into 4groups, each groups consist of 6 rats. Group I was as negative control group givenCMC-Na 1%, group II was as positive control group given glibenklamid dose 1,35mg/kgBB, group III and IV where given ethanolic extract of kacapiring leaf dose 500mg/kgBB and 250 mg/kgBB. Glibenklamid and exstract are given orally 60 minutesbefore glucose. Blood was taken from orbitalis sinus at minute (-90), (-60), 0, 30, 60,120, 180, 240, and 300. Blood glucose level was determined with GOD PAP enzymaticmethod, absorbance was observed using spectrophotometer at 500 nm. The result of the study was performed by giving ethanolic extract of kacapiring leaf dose 500 mg/kgW and 250 mg/kgW had antihiperglycemic effect. Ethanolic extract of kacapiring leaf dose500 mg/kgW and 250 mg/kgW could reduce blood glucoce level 58,97% and 80,60% compared with glibenklamid dose 1,35 mg/kgW could reduce blood glucoce level73,93%.